ANALYSIS OF CHEMOKINE GENE EXPRESSION IN LUNG CELLS BY POLYMERASE CHAIN REACTION - Petřek, Martin (Biomedical papers, 1999)
The article describes a polymerase chain reaction (PCR) based method for semiquantitative assessment ofmRNA expression for chemotactic cytokines in the lower respiratory tract cells. Cytokine mRNA was detectedusing PCR preceded by reverse transcription of mRNA into cDNA. The procedures of RNA extraction and ofreverse transcription-PCR assay are described in the first part of the article. The second part demonstratesoptimalisation experiments performed to ensure specificity, accuracy and reproducibility of the RT-PCR assay anddiscuss the approach to mRNA quantification using normalisation of cytokine mRNA expression to the expressionof b-actin mRNA.
Keywords: Chemokines / mRNA expression / Reverse transcription - PCR / Optimalisation